2023
DOI: 10.3389/fendo.2023.1159055
|View full text |Cite
|
Sign up to set email alerts
|

Association between weight-adjusted-waist index with hepatic steatosis and liver fibrosis: a nationally representative cross-sectional study from NHANES 2017 to 2020

Abstract: BackgroundThe negative effects of obesity on hepatic steatosis and fibrosis have received considerable attention in recent years. The weight-adjusted-waist index (WWI) reflects weight-independent centripetal obesity. Herein, we provide the first investigation of a link between WWI, hepatic steatosis, and liver fibrosis.MethodsWe used data from the National Health and Nutrition Examination Survey 2017-2020 to conduct a cross-sectional study. The linear relationship between WWI, controlled attenuation parameters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 34 publications
1
7
0
Order By: Relevance
“…Building upon Shen et al's study, our research further evaluated the association of WWI with NAFLD, yielding significant positive associations. These findings provided further support for Shen et al's results [ 30 ], suggesting that WWI was a useful index for evaluating liver fat deposition. However, it is noteworthy that our study also identified a nonlinear relationship between WWI and NAFLD; whether in the entire population, men or women, there was a gradual attenuation of the positive association when WWI approached 10, which contrasted with Shen et al's findings.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Building upon Shen et al's study, our research further evaluated the association of WWI with NAFLD, yielding significant positive associations. These findings provided further support for Shen et al's results [ 30 ], suggesting that WWI was a useful index for evaluating liver fat deposition. However, it is noteworthy that our study also identified a nonlinear relationship between WWI and NAFLD; whether in the entire population, men or women, there was a gradual attenuation of the positive association when WWI approached 10, which contrasted with Shen et al's findings.…”
Section: Discussionsupporting
confidence: 85%
“…They quantified liver fat deposition and fibrosis using vibration-controlled transient elastography and found a significant positive correlation of WWI with liver fat deposition. Moreover, by fitting the smooth curve, they also found a U-shaped nonlinear correlation of WWI with liver fibrosis, and on both sides of WWI equal to 10.92, the WWI-related liver fibrosis risk showed an opposite trend [ 30 ]. Building upon Shen et al's study, our research further evaluated the association of WWI with NAFLD, yielding significant positive associations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Substantial large-sample observational clinical studies have linked WWI to the development and comorbidities of a variety of clinical conditions, including NAFLD. A crosssectional analysis similarly using NHANES 2017-2020 suggested that WWI was associated with hepatic steatosis, independently of BMI [37]. Another cross-sectional study, also using NHANES 2017-2020, showed that WWI was signi cantly and positively associated with NAFLD and liver brosis [38].…”
Section: Discussionmentioning
confidence: 99%
“…The WWI offers a more nuanced distinction between fat and muscle mass, focusing primarily on abdominal obesity independent of body weight (7,8). Additionally, emerging evidence has substantiated the notion that an elevation in the WWI index poses a substantial risk factor for metabolic disorders, including diabetes and non-alcoholic fatty liver disease (8)(9)(10)(11). Consequently, it is of paramount importance to delve deeper into its correlation with DKD within the diabetic population.…”
Section: Introductionmentioning
confidence: 99%